Factors Influencing Toddler Visit to Integrated Healthcare Center in Sukabumi District - Pratiwi, Kusuma Putri (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The purpose of this study was to determine the effect of knowledge, motivation, the role of health workers, and family support on toddler visit to integrated healthcare center in Sukabumi district. Methods:  This type of research was conducted with a cross sectional design. The population was all mothers of toddlers with a sample of 225, using proportional random sampling technique. Statistical analysis to determine the effect using logistic regression. Results:  There is an influence of knowledge (p=0.000), motivation (p=0.000), the role of health workers (p=0.000) and family support (p=0.000) on toddler posyandu visits in Sukamanis Village, Kadudampit Health Center Working Area, Sukabumi Regency. Conclusion:  Knowledge, motivation, role of health workers and family support influenced toddler posyandu visits in Sukamanis Village, Kadudampit Health Center Working Area, Sukabumi District.